(untitled) (Fiep Bulletin - online, 2015)
The aim of the present descriptive study is to determine physical activity and stress levels, according to sex and age, of professors and staff working in college courses at the Universidade Luterana do Brasil, Canoas, RS, in 2005. It was studied 74 professors and other staff from the university selected through the convenience sampling method. The instruments applied were the short form of the IPAQ and Lipp’s Stress Symptoms Inventory for Adults (LSSI). The statistical tools used for the data analysis were mean, standard deviation, percentage, frequency distribution, the chi-square test and variance analysis using the SPSS 12.0 software. It was found that of the 74 subjects investigated 40 % were insufficiently active; 47 did not show stress, 18 were in the resistance phase, 7 in the exhaustion phase and 2 in the alert phase. Using the chi-square statistical test, it was revealed that there is no significant connection between physical activity level and the occurrence of stress (p=0.67). Similarly, the physical activity level of stressed individuals was not significantly associated with their sex (p=0.71). In the same way, no suggestive connection was found between job and kind of stress symptom (p=0.21). Through variance analysis, it could be inferred there was no significant difference between the physical activity level of individuals who showed stress and their average age (p=0.49).